No association between polymorphisms in the BDNF gene and age at onset in Huntington disease - Kraus Peter H; Andrich Jürgen; Saft Carsten; Wieczorek Stefan; Akkad Amer D; Mai Maren; Epplen Jörg T; Arning Larissa (BMC, 2006)
Abstract Background Recent evidence suggests that brain-derived neurotrophic factor (BDNF) is an attractive candidate for modifying age at onset (AO) in Huntington disease (HD). In particular, the functional Val66Met polymorphism appeared to exert a significant effect. Here we evaluate BDNF variability with respect to AO of HD using markers that represent the entire locus. Methods Five selected tagging polymorphisms were genotyped across a 65 kb region comprising the BDNF gene in a well established cohort of 250 unrelated German HD patients. Results Addition of BDNF genotype variations or one of the marker haplotypes to the effect of CAG repeat lengths did not affect the variance of the AO. Conclusion We were unable to verify a recently reported association between the functional Val66Met polymorphism in the BDNF gene and AO in HD. From our findings, we conclude that neither sequence variations in nor near the gene contribute significantly to the variance of AO.